The Relationship between Empathy and Aggressive Driving Behavior in Late Adolescents in Makassar City - Caroline, Cindy; Firdaus, Faradillah; ., Irdianti (Polteknik Ilmu Pemasyarakatan, 2024)
The increase in motorbike vehicles continues to occur every year. This is because aggressive driving behavior in late adolescents in Makassar City. The subjects of this research consisted of 260 people aged 18-22 years who rode motorbikes in Makassar City. This research uses an aggressive driving scale and an empathy scale. The sampling technique used accidental sampling technique with data analysis using the Spearman Rho technique using SPSS IBM 24.0 for Windows. The results show that the R coefficient value is -0.375 and the p value = 0.000 <0.05, meaning that there is a negative relationship between empathy and aggressive driving behavior in late teens. The higher the empathy, the lower the aggressive driving behavior, and vice versa. The effective contribution (R Squaredmotorbikes make it very easy for individuals to carry out daily activities. However, teenagers' involvement in aggressive driving has the potential to cause accidents. The need for empathy to position oneself so as to reduce the level of aggressiveness when driving. This research aims to determine the relationship between empathy and) of the empathy variable to aggressive driving behavior is 19.6%. The implications of this research provide an overview of the relationship between empathy and aggressive driving behavior, a scientific basis for related parties in taking management policies related to driving, as a reference in providing education so that they can be empathetic when driving.